Measurement of Efficiency and Productivity of Amil Zakat Institutions in Indonesia by using Data Envelopement Analysis Methods and Malmquist Productivity Index - Selvia Rustyani; Suherman Rosyidi (Universitas Airlangga, 2019)
This study aims to measure the level of efficiency and productivity of the amil zakat institution in Indonesia. This research is a quantitative research using Data Envelopment Analysis (DEA) and Malmquist Productivity Index (MPI) methods. There are six institutions of amil zakat (LAZ in Indonesia, namely Yayasan Dana Sosial Al-Falah (YDSF), Al-Azhar Peduli Ummat, Aksi Cepat Tanggap (ACT), Yayasan Rumah Yatim Arrohman Indonesia, Pos Kemanusiaan Peduli Ummat (PKPU), and Rumah Zakat Indonesia with 2014 - 2016 annual data as the number of DMUs (desicion making units). This study uses an intermediation approach in determining the variables. The input variables of this research are Collected Funds (X1), Total Costs (X2), and Amil Receipts (X3), while the output variables are Funds Disbursed (Y1), and Total Assets (Y2). There were two LAZs that experienced inefficiencies in 2014 and 2015, namely LAZ YDSF and ACT. Meanwhile, in 2016, all LAZ have achieved optimal levels of efficiency. The results of the MPI analysis show that in the first year there were two LAZs that experienced a decline in productivity, namely LAZ Al-Azhar and PKPU. The other four LAZs experienced increased productivity, namely LAZ YDSF, ACT, Rumah Yatim, and Rumah Zakat. In the second year, there were three LAZs who experienced increased productivity, namely LAZ Al-Azhar, PKPU, and Rumah Zakat. Meanwhile, three other LAZ experienced a decrease in productivity, namely LAZ YDSF, ACT, and Rumah Yatim.Keywords: Efficiency, Productivity, LAZ, DEA, MPIREFERENCES Al-Qur’an dan Terjemah.Al-Hadits.Abd Wahab, Norazlina dan Abdul Rahman Abdul Rahim. 2013. Determinants of Efficiency of Zakat Institutions in Malaysia: A Non-parametric Approach, Asian Journal of Business and Accounting 6 (2), hlm. 33 – 64.Aini, Novi Nurul. 2012. Efisiensi Lembaga Zakat Nasional Menggunakan Metode Data Envelopment Analysis Periode 2008-2009. Skripsi. Surabaya: Universitas Airlangga.Akbar, Nasher. 2009. Analisis Efisiensi Organisasi Pengelola Zakat Nasional dengan Pendekatan Data Envelopment Analysis. Jurnal TAZKIA Islamic Finance and Business Review, Vol. 4 No. 2, 760 – 784.Aksi Cepat Tanggap https://act.id/Al-Azhar Peduli Ummat https://alazharpeduli.com/Al-Parisi, Salman. 2017. Analisis Determinan Lembaga Zakat di Indonesia dan Tingkat Produktivitas-nya. Bogor: Smart Consulting.Ali, Mahbubi, dan Ascarya. 2010. Analisis Efisiensi Baitul Maal Wat Tamwil Dengan Pendekatan Two Stage Data Envelopment Analysis (Studi Kasus Kantor Cabang BMT MMU dan BMT UGT Sidogiri). Jurnal TAZKIA Islamic Finance and Business Review, Vol. 5 No. 2, 110 – 125.Badan Amil Zakat Nasional https://pusat.baznas.go.id/Badan Pusat Statistik. https://www.bps.go.id/Banker, R.D., Charnes, A., and Cooper, W.W. 1984. “Some Models for Estimating Technical and Scale Inefficiency in Data Envelopment Analysis”, Management Science, 30 (9), 1078-92.Beik, Irfan Syauqi, dkk. 2012. Economic Estimation and Determinations of Zakat Potential in Indonesia. Caves et al. 1982. “The Economic Theory of Index Number and The Measurement of Input, Output, and Productivity”. Econometrica, 50(6):1393-1414.Charnes, A., W.W. Cooper, and E. Rhodes. 1978. “Measuring the Efficiency of Decision Making Units”, European Journal of Operation Research, 2, 6, 429-44.Coelli, T.J, D.S.P. Rao, and G.E. Battese. 1998. Introduction to Efficiency and Productivity Analysis. Boston: Kluwer Academic Publisher.Coelli, T .J, 1996. A Guide to DEAP Version 2.1: A Data Envelopment Analysis (Computer) Program. Armidale: CEPA The University of New England.Difanda, Renaldy Dafi. 2017. Analisis Efisiensi BAZNAS Provinsi dengan Metode Data Envelopment Analysis (DEA). Skripsi. Surabaya: Universitas Airlangga.Farrell, M.L. 1957. “The Measurement of Productive Efficiency”, Journal of The Royal Statistical Society, 120, p.253-281.Kamus Besar Bahasa Indonesia (KBBI) daring, (http://kbbi.web.id/pusat, diakses 19 Juli 2018).Krishnasamy, Geeta, dkk. 2003. Malaysian Post Merger Bank’s Productivity: Application of Malmquist Productivity Index. Petaling Jaya: Monash University Malaysia.Maulana, Ahmad. 2017. Efisiensi Kinerja Lembaga Zakat Nasional (Studi Kasus: YDSF, Yatim Mandiri, & Lazisnu). Skripsi. Surabaya: Universitas Airlangga.Mubarok, Abdulloh, dan Baihaqi Fanani. 2014. Penghimpunan Dana Zakat Nasional (Potensi, Realisasi, dan Peran Penting Organisasi Pengelola Zakat). Jurnal PERMANA, Vol. V, No.2, hlm. 14.Munir, Misbahul dan A. Djalaluddin. 2006. Ekonomi Qur’ani: Doktrin Reformasi Ekonomi dalam Al-Qur’an. Malang: UIN Malang Press.Pos Kemanusiaan Peduli Ummat https://pkpu.org/PUKAS BAZNAS. 2016. Outlook Zakat Indonesia 2017. Jakarta: BAZNAS.Qardhawi, Yusuf. 2007. Hukum Zakat, (terj. Salman Harun, dkk.), Bogor: Pustaka Litera Antarnusa.Rahmayanti, Annisa. 2014. Efisiensi Lembaga Amil Zakat Dalam Mengelola Dana Zakat di Indonesia (Studi Kasus: PKPU, Rumah Zakat, dan BAMUIS BNI). Skripsi. Jakarta: UIN Syarif Hidayatullah.Republik Indonesia. Undang-undang Nomor 23 Tahun 2011 tentang Pengelolaan Zakat. 2011. Jakarta: kemenag.go.id.________. Undang-undang Nomor 38 Tahun 1999 tentang Pengelolaan Zakat. 1999. Jakarta: dpr.go.id.________. Peraturan Pemerintah Nomor 14 Tahun 2014. 2014. Jakarta: pid.baznas.go.id.________. Pedoman Transliterasi Arab-Latin. Surat Keputusan Bersama Menteri Agama RI dan Menteri Pendidikan dan Kebudayaan RI Nomor 158/1987 dan0543 b/U/1987, tanggal 22 Januari 1988.Rosyidi, Suherman. 2006. Pengantar Teori Ekonomi. Edisi Revisi. Jakarta: PT Raja Grafindo Persada.Rumah Zakat Indonesia https://rumahzakat.org/Rusdyana, Aam. 2017. Pelatihan DEA dan Indeks Malmquist, Surabaya: Universitas Airlangga.Sedarmayanti. 2001. Sumber Daya Manusia dan Produktivitas Kerja. Bandung: Mandar Maju.Sugiyono.2012. Metode Penelitian Kuantitatif, Kualitatif, dan R & D. Bandung: Alfabeta.Surjaningsih, Ndari, dan Bayu Panji Permono. 2014. “Dinamika Total Factor Productivity Industri Besar dan Sedang Indonesia”. Buletin Ekonomi Moneter dan Perbankan, hlm. 277 – 308. Jakarta: Bank Indonesia.Wandayati, Nur Ika. 2018. Analisis Efisiensi Lembaga Amil Zakat Nasional di Indonesia dengan Metode Data Envelopment Analysis Tahun 2010-2016. Skripsi. Surabaya: Universitas Airlangga.Wahyuny, Ikka Nur. 2015. Analisis Efisiensi Organisasi Pengelola Zakat Nasional dengan Metode Data Envelopment Analysis (Studi di Badan Amil Zakat Nasional, Dompet Dhuafa, dan Lazis Nahdlatul Ulama Periode 2013.Skripsi. Yogyakarta: Universitas Negeri Yogyakarta.Yayasan Dana Sosial Al-Falah https://ydsf.org/Yayasan Rumah Yatim Ar-rohman Indonesia https://rumah-yatim.org/2000-2015. Frontier Analyst Manual version 4.3. Banxia Holdings Ltd. (https://banxia.com/downloads/)